The Coyaba Chronicles refelctions on the black expereince in the 20th century (South Africa David Philip Publishers, 2000)
"The Coyaba Chronicles: Reflections on the Black Experience in the Twentieth Century" is both personal memoir and a powerful meditation on what W.E.B. Dubois defined at the beginning of the century as "the problem of the colour line; of the relations between the lighter and darker races of man". Using Dubois as a point of departure, Abrahams writes passionately, about the inherent "wrongness" of racial hatred and contemplates such timeless questions as: "Why was colour the most crucial issue of our century?" and "When will we get over the deep psychic and emotional damage done by the racial experience?" This is one of the major themes of the memoir - the quest for an intellectual identity - a challenge that faces people of colour in first and third-world countries. "The Coyaba Chronicles" is also the personal journey of Peter Abrahams. It is the odyssey of a young South African who works for a time as a seaman, leaving his homeland for wartime Britain and post-war France to become a writer; it is the story of his personal relationships with the Black literati of the day and his involvement in the pan-Africanist movement of the 1950's - allowing for his fascinating personal pen-portraits of George Padmore, W.E.B. Dubois, Julius Nyerere, Kwame Nkrumah, Richard Wright and Langston Hughes. It is how the journey takes him to the Caribbean island of Jamaica, where he and his wife Daphne and their three children find sanctuary from racial divisiveness at "Coyaba" in the hills of St Andrew.
Keywords: World War, Cold War Mandela, Nelson, 1918-